Une expérience pédagogique musicale en Grande Section Maternelle et Cours Préparatoire - Marie-Renée Guilloret (Nantes Université, 2013)
During a learning experience which took place first in a nursery, and then in a primary school, pupils have composed their own pieces of music. We are asking about the nature of the processes used. According to Vygotsky, culture is considered as the core of proximal development zones, allowing a learner to interact with a more able one. This guided us towards the identification of processes of using resources. We then spotted how pupils interact with musicians, their pairs and the other resources of the setting. As we consider the gap between intention, resources and production, we move on from spotting how pupils get access to the resources to how they adjust themselves to the task at hand. These processes are presented as the markers of a creative dynamic, operating in a setting which promotes the migration of resources.